Morphological differences between avian influenza viruses grown in chicken and duck cells, a comparative study - Al-Mubarak, Firas (2014)
The major reservoirs for most influenza A virus subtypes are wild aquatic birds, especially ducks. However, they are typically resistant to the effects of the infection and usually do not develop clinical disease. In contrast, some influenza viruses cause severe illness or even death in susceptible hosts like chickens and turkeys. Paradoxically, infection of primary duck cells results in rapid cell death, whereas in chicken cells, death occurs less rapidly. Duck cells produce fewer infectious virions in comparison with the longer surviving chicken cells. In order to understand this variation in infectious virus production, chicken and duck embryo fibroblast cells (CEF and DEF) were infected with low pathogenic avian H2N3, and the viruses produced from the two hosts ware characterised. Infectious virus production from chicken cells was significantly greater than that observed from duck cells, from 8–48 hr after infection. Influenza matrix gene and protein expression, analysed by quantitative real time PCR and western blotting of culture supernatants, showed comparable levels between species at 8 and 24 hr post infection. These findings led to investigation of virus budding and morphology following infection of duck and chicken cells with the virus. Differences in morphology of released virions were observed. Budding viruses from duck cells were elongated, while chicken cells produced almost spherical virions. There was a similar clear difference in virus morphology in the duck and chicken culture supernatants. Spherical viruses were observed in chicken supernatants while duck cell supernatants contained pleomorphic virions. No differences between any genes of chicken– and duck–derived viruses were found, suggesting that host cell determinants might be responsible for such variations in virus morphology. DEF cells showed extensive production of filamentous or short filament virions following infection with filamentous (equine H3N8) and non–filamentous (avian H2N3) virus strain, respectively. This was observed even after actin disruption with cytochalasin D (Cyt.D). CEF cells infected with equine H3N8 virus produced extensive filamentous virus, which decreased markedly after disruption of actin with Cyt.D, whereas, following infection with H2N3, spherical virions were observed in the presence or absence of the actin inhibitor. Cells were also transfected with green fluorescent protein – microtubule-associated protein 1A/1B-light chain 3 (GFP–LC3) expression vector and then infected or mock infected with avian H2N3. Short filaments were observed from untransfected and transfected duck cells, while spherical and short filaments were observed from untransfected and transfected chicken cells, respectively. Filamentous virus formation could be enhanced as a result of autophagy which is more marked in duck cells than chicken cells. Further studies such as studying the structure of chicken and duck fibroblast cell membranes, the use of other drugs that inhibit actin in a mechanistically different way, and the role of other cellular proteins in modulating virus morphology should be considered.